Prospective Endoscopic Activity Assessment for Eosinophilic Gastritis in a Multisite Cohort. (20th March 2022) - Hirano, Ikuo; Collins, Margaret H.; King, Eileen; Sun, Qin; Chehade, Mirna; Abonia, J Pablo.; Bonis, Peter A.; Capocelli, Kelly E.; Dellon, Evan S.; Falk, Gary W.; Gonsalves, Nirmala; Gupta, Sandeep K.; et al.
Abstract : INTRODUCTION: Eosinophilic gastritis (EG) is a chronic inflammatory disease of the stomach characterized by eosinophil-predominant gastric mucosal inflammation and gastrointestinal symptoms. The aim of this study was to prospectively evaluate endoscopic features in a large series of children and adults with EG to better understand the endoscopic manifestations and develop a standardized instrument for investigations. METHODS: Data were prospectively collected as part of the Consortium for Eosinophilic Gastrointestinal Disease Researchers, a national collaborative network. Endoscopic features were prospectively recorded using a system specifically developed for EG, the EG Endoscopic Reference System (EG-REFS). Correlations were made between EG-REFS and clinical and histologic features. RESULTS: Of 98 patients with EG, 65 underwent assessments using EG-REFS. The most common findings were erythema (72%), raised lesions (49%), erosions (46%), and granularity (35%); only 8% of patients with active histology (≥30 eosinophils/high-power field) exhibited no endoscopic findings. A strong correlation between EG-REFS scores and physician global assessment of endoscopy severity was demonstrated (Spearman r = 0.84, P < 0.0001). The overall score and specific components of EG-REFS were more common in the antrum than in the fundus or body. EG-REFS severity was significantly correlated with active histology, defined by a threshold of ≥30 eosinophils/high-power field ( P = 0.0002). DISCUSSION: Prospective application of EG-REFS identified gastric features with a strong correlation with physician global assessment of endoscopic activity in EG. Endoscopic features demonstrated greater severity in patients with active histology and a predilection for the gastric antrum. Further development of EG-REFS should improve its utility in clinical studies.